Plasticity of hematopoietic stem cells. Issue 2 (June 2015) - Ogawa, Makio; LaRue, Amanda C.; Mehrotra, Meenal
Abstract: Almost two decades ago, a number of cell culture and preclinical transplantation studies suggested the striking concept of the tissue-reconstituting ability of hematopoietic stem cells (HSCs). While this heralded an exciting time of radically new therapies for disorders of many organs and tissues, the concept was soon mired by controversy and remained dormant. This chapter provides a brief review of evidence for HSC plasticity including our findings based on single HSC transplantation in mouse. These studies strongly support the concept that HSCs are pluripotent and may be the source for the majority, if not all, of the cell types in our body.